Penegakan Hukum Tindak Pidana Pemalsuan Polis Asuransi - Husna Husna; Muh Endriyo Susila (Media of Law and Sharia, 2022)
The existence of insurance is very much needed by the community, especially in large-scale economic activities. The existence of community activities allows for a large risk, so insurance can be a solution to protect the object of insurance. Unfortunately, the use of insurance policies is often misused, namely falsification of insurance policies. Forgery of insurance policies is a crime that has implications for the loss of trust for the parties to the insurance agreement. This study aims to understand and find out how law enforcement against the crime of counterfeiting insurance policies at PT. Harta Aman Pratama, Tbk. Yogyakarta Branch. This research is an empirical juridical research, namely research that explores both primary data sources and secondary data in the form of legal materials. One of the legal materials studied is the decision of the Sleman District Court No. 529/Pid.Sus/2016/PN Smn. The results showed that law enforcement against the crime of insurance policy forgery that occurred at PT Harta Aman Pratama, Tbk Yogyakarta Branch was carried out through the process of investigation, prosecution, examination of court hearings and implementation of court decisions. The perpetrator was charged with committing a criminal act of policy forgery as stipulated in Article 78 of Law Number 40 of 2014 concerning Insurance jo. Article 64 paragraph (1) of the Criminal Code. During the examination at the Sleman District Court, the defendant was found guilty and sentenced to imprisonment for 5 (five) months and a fine of Rp. 10,000,000. (Ten million rupiah). The convict served his prison sentence at the Cebongan Prison, Sleman.